GJB1 Mutation-A Disease Spectrum: Report of Case Series - Niu, Jingwen; Dai, Yi; Liu, Mingsheng; Li, Yi; Ding, Qingyun; Guan, Yuzhou; Cui, Liying; Jin, Liri (Frontiers in Neurology, 2020)
Introduction: Patients with GJB1 mutations manifested as pure central nervous system (CNS) involvement without peripheral neuropathy have not been adequately reported. To expand the disease spectrum of GJB1 mutations, we report a case series. Methods: Eleven patients from 9 families with GJB1 mutations were reviewed. The clinical manifestations, electrophysiological studies, and gene tests were summarized. Results: Nine patients had peripheral neuropathy, one patient had both peripheral neuropathy and mild cognitive impairment, and one patient had recurrent episodic limbs weakness and aphasia with normal electrophysiological study, indicating CNS involvement only. Discussion: GJB1 mutations form a clinical spectrum, including most patients with peripheral nerve involvement, those with both peripheral neuropathy and CNS involvement, and patients with CNS involvement only.